1993
DOI: 10.1116/1.586915
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling microscopy of point defects on GaAs(110)

Abstract: The structure of point defects situated at nominal arsenic or gallium sites on the (110) cleavage face of GaAs has been studied by scanning tunneling microscopy (STM). Alternate-bias imaging was used to simultaneously resolve the arsenic and gallium sublattices corresponding to filled and empty states, respectively, on both p- and n-type material. There is an interesting symmetry in the characteristic features associated with the most commonly observed defect of each type. Both types appear in the STM images a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 0 publications
2
36
0
Order By: Relevance
“…Here, a dark contrast on an array of about 3 ϫ 3 missing unoccupied dangling bonds has been interpreted as the signature of a Ga vacancy. 7 That signature does not agree with the signature of the complex, but we suggest that signature to be caused by hydrogen adsorption. 31 Another group interpreted the X-shaped dark contrast to be the signature of a Ga vacancy.…”
Section: Simulated Stmmentioning
confidence: 54%
See 1 more Smart Citation
“…Here, a dark contrast on an array of about 3 ϫ 3 missing unoccupied dangling bonds has been interpreted as the signature of a Ga vacancy. 7 That signature does not agree with the signature of the complex, but we suggest that signature to be caused by hydrogen adsorption. 31 Another group interpreted the X-shaped dark contrast to be the signature of a Ga vacancy.…”
Section: Simulated Stmmentioning
confidence: 54%
“…[1][2][3][4][5][6] In contrast to the anion vacancy, there are only a few studies of cation vacancies. In scanning tunneling microscopy ͑STM͒ images of the unoccupied states of GaAs ͑110͒ surfaces, two features interpreted as being caused by Ga vacancies have been reported: Lengel et al 7 observed a dark contrast that appears on an array consisting of about 3 ϫ 3 missing unoccupied dangling bonds, whereas Ebert and Urban 8 and Domke et al 9 observed an X-shaped dark contrast consisting of one missing unoccupied dangling bond.…”
Section: Introductionmentioning
confidence: 99%
“…14 The currently published experimental values for the screening length ͑which determines the extend of the screened Coulomb potential͒ at GaAs and InP͑110͒ surfaces are constantly between 1 and 2 nm independent of the defect and doping concentrations investigated. [9][10][11][12][13][14] This disagrees with theoretical expectations, which predict a strong increase in the screening length with decreasing carrier concentration. Despite theoretical efforts to clarify this inconsistency by assuming additional screening by defect-induced carriers at the surface, 7,8 no understanding of the apparently short screening length at negligibly low defect concentrations was achieved.…”
Section: Introductionmentioning
confidence: 84%
“…First, the screening potentials are frequently approximated by height profiles taken in constant-current STM images. [9][10][11][12][13][14] Second, the close proximity of the STM tip near the surface induces localized band bendings, [15][16][17][18] which modify the potential around charged defects significantly and thus the screening cannot be probed quantitatively. Third, the limited signal to noise ratio of barrier height or surface photovoltage measurements [19][20][21] restrict a quantitative data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, As vacancies have been reported in GaAs [21][22][23] and InAs [24], P vacancies in InP [25][26][27] and GaP [26,28], Sb vacancies in InSb [29,30], and Ga vacancies in GaAs [22,31,32] and GaP [33] (110) surfaces. Recently, vacancies have also been observed in CdSe and CdS cleavage surfaces [34].…”
Section: Observation Of Surface Vacancies With Atomic Resolutionmentioning
confidence: 99%